PENGGUNAAN METODE COUNTING BLOOM FILTER PADA APLIKASI INTRUSION DETECTION SYSTEM PADA BASIS DATA - Eric Winata Jonathan; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
This intrusion detection system for security in database was developed to help client(s) that uses a database to find out what changes have been made in the database. Intrusion detection system using Counting Bloom Filter (CBF), with transaction records  as training data input to create profile transactions automatically as a set of transactions that will be stored in the CBF, the program will compare the transactions made with the user profile transactions in the detection stage. Testing is done by inserting dummy training datas and transactions that have been known how many malicious transaction in that transactions. Testing is carried out on thirty transaction data that known to be intrusion or not and intrusion detection systems can read all invalid transactions with success rate of 100%. KeywordsCounting Bloom Filter, Database security, Intrusion Detection System, Transaction profile, Web Service.